INTERACTION OF LIPOSOMES WITH CANCER CELLS: INFLUENCE OF LIPOSOME SURFACE PROPERTIES ON CELLULAR UPTAKE - KUMAR SANDEEP (International Journal of Pharma and Bio Sciences, 2016)
The enormous progress in understanding the basic biology of cancer cells and the rapid advancement of nanotechnology showed immense potential for improving conventional ways of treating cancer. The understanding of how liposomes interact with cancer cells in a biological environment is a serious concern and need substantial knowledge to develop novel drug delivery vehicles for cancer cell specific delivery while sparing off adjacent normal tissues. This review summarizes the scientific reports on liposome-cell interactions with a focus on the effect of liposome size, surface charge and lipid composition of liposomes on the interaction with different kinds of cancer cells.